1999
DOI: 10.1086/306752
|View full text |Cite
|
Sign up to set email alerts
|

Structure‐dependent Photostability of Polycyclic Aromatic Hydrocarbon Cations: Laboratory Studies and Astrophysical Implications

Abstract: Following a previous experimental study of the photostability of a series of polycyclic aromatic hydrocarbons (PAHs) this work extends to irregularly shaped PAHs, methyl-substituted PAHs, and related compounds. A photostability index R has been devised, which measures the propensity for H-loss of PAH monocations relative to that for regular catacondensed or pericondensed PAHs containing the same number of atoms. This index is also valid, to a good approximation, for neutral PAHs. Structural e †ects (presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
126
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(138 citation statements)
references
References 56 publications
11
126
1
Order By: Relevance
“…In contrast, Jochims et al (1999) had observed in their experiments that the minimum photon energy causing the loss of a H atom by a photoionized PAH molecule was at least 2 eV lower when the molecule carried a methyl, a vinyl, or a phenyl group. Prior to the latter study, and Gotkis et al (1993) had found in TPIMS experiments that the minimum photon energy for H atom loss upon photoionization was also at least 2 eV lower in 1-and 2-methylnaphthalene than in naphthalene, for any time scale.…”
Section: Appearance Energiesmentioning
confidence: 89%
See 3 more Smart Citations
“…In contrast, Jochims et al (1999) had observed in their experiments that the minimum photon energy causing the loss of a H atom by a photoionized PAH molecule was at least 2 eV lower when the molecule carried a methyl, a vinyl, or a phenyl group. Prior to the latter study, and Gotkis et al (1993) had found in TPIMS experiments that the minimum photon energy for H atom loss upon photoionization was also at least 2 eV lower in 1-and 2-methylnaphthalene than in naphthalene, for any time scale.…”
Section: Appearance Energiesmentioning
confidence: 89%
“…Non-statistical processes such as direct dissociation from an excited repulsive state might happen although previous works have favored the statistical path considered here (see Jochims et al 1994;Allain et al 1996a;Le Page et al 2001). Figure 6 presents for comparison some of the photostability index values determined by Jochims et al (1999) for various regular PAH molecules and derivatives along with those we have derived by considering that the internal thermal energy of the molecules reflected their translational temperature. It also reports the E E c, H * --differences.…”
Section: Photostabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…The photoionization quantum yield of PAHs is an important parameter in astrophysical modeling of their formation and destruction, and has been measured for a series of PAHs in the 5-25 eV range by Jochims, Baumgartel & Leach (1996), who also established 'rules of thump' for other species. Another important parameter is the structure-dependent photostability of PAH cations, studied by Allain et al (1996a,b), Allain & Leach (1997) and Jochims, Baumgartel & Leach (1999). Work has also been carried out on the dissociative ionization of PAHs in the 8-35 eV photon energy range (Jochims et al 1997).…”
Section: Electronic Spectramentioning
confidence: 99%